Championing Inclusion : Understanding LGBT Diversity and Social Support in the Workplace - Amancherla, Sowmya; Balasundaram, Sathiyaseelan; Basavaraj, Santosh (Prabandhan: Indian Journal of Management, 2024)
Purpose : This study investigated the impact of LGBT diversity management practices on the acceptance of LGBT employees by non-LGBT peers in Indian organizations. Based on classical social support theory and signaling theory, the study focused on how social support from co-workers and supervisors influenced this relationship. Methodology : Data were collected by surveying 546 employees across nine tech parks in the Indian IT/ITES sector. Partial Least Square (PLS) predictions and structural equation modeling (SEM) were conducted using Smart PLS version 4. Mediation and moderation analyses were also performed. Findings : The results exhibited that LGBT diversity management positively affected the acceptance of LGBT peers in the workplace (β = 0.298; t = 6.314; p = 0.00). Supervisor support was a complementary mediator (VAF = 0.33), while co-worker support moderated the association (β = 0.514; t = 15.916; p = 0.00). Practical Implications : The study presented managerial acumen regarding how social support from supervisors and co-workers enriched the efficacy of diversity management approaches. These outcomes were predominantly pertinent for organizations considering adopting an all-encompassing place of work for LGBT employees. Originality : This investigation delivered a distinctive offering by inspecting the role of social support in LGBT diversity management among the Indian IT segment. While based in Bengaluru, the study encouraged further investigation into additional businesses and geographies.